2019
DOI: 10.1007/s40139-019-00193-7
|View full text |Cite
|
Sign up to set email alerts
|

Biospecimen Science of Blood for cfDNA Genetic Analyses

Abstract: Purpose of Review cfDNA is increasingly used for biomonitoring oncological diseases or pregnancy status by different genetic analyses. Uncontrolled pre-analytical variability impacts the quality and quantity and subsequently undermines the utility of this analyte. In this review, we summarize critical pre-analytical factors to be addressed, to avoid irreproducible results. Recent Findings cfDNA quantity and quality can be impacted by the in vivo condition of the donor and the ex vivo biospecimen handling prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…As generally seen for liquid biopsy samples [ 50 – 52 ], the amount of total cfDNA extracted per millilitre (ml) of plasma was low ( Fig 6 ). For cohort I, the median amount of DNA extracted per ml of plasma was 11.30 ng [2.33ng/ml;86.28ng/ml].…”
Section: Resultssupporting
confidence: 55%
“…As generally seen for liquid biopsy samples [ 50 – 52 ], the amount of total cfDNA extracted per millilitre (ml) of plasma was low ( Fig 6 ). For cohort I, the median amount of DNA extracted per ml of plasma was 11.30 ng [2.33ng/ml;86.28ng/ml].…”
Section: Resultssupporting
confidence: 55%
“…The isolation of cfDNA from plasma samples instead of serum is also preferable, given that it avoids the release of cellular DNA from lysing cells during the clotting process. In addition, due to low concentrations, extraction methods must guarantee high yields of cfDNA [92]. The low quantities and small fraction of ctDNA in circulation require the use of highly sensitive detection techniques, such as droplet digital Polymerase Chain Reaction (ddPCR), Next Generation Sequencing (NGS) [41] or BEAMing (beads, emulsion, amplification and magnetics) [12].…”
Section: Advantages and Disadvantages Of Liquid Biopsiesmentioning
confidence: 99%
“…By ‘lifestyle factor’, we refer to all external variables that involve individual choice, such as exercise, alcohol consumption, occupation and smoking. We have chosen to include only studies conducted on plasma and exclude all studies on serum as serum has been shown to be the less preferred substrate due to its propensity for leukocyte DNA contamination and dependence on processing time ( Ammerlaan and Betsou, 2019 ; Trigg et al, 2018 ; Warton et al, 2014 ). The use of serum was the only exclusion criterion that we imposed.…”
Section: Introductionmentioning
confidence: 99%